Knowledge about the Developmental Origins of Health and Disease is independently associated with variation in diet quality during pregnancy. Issue 2 (12th December 2019) - McKerracher, Luseadra; Moffat, Tina; Barker, Mary; McConnell, Meghan; Atkinson, Stephanie A.; Murray‐Davis, Beth; McDonald, Sarah D.; Sloboda, Deborah M.
Abstract: Environmental factors affecting development through embryogenesis, pregnancy, and infancy impact health through all subsequent stages of life. Known as the Developmental Origins of Health and Disease (DOHaD) hypothesis, this concept is widely accepted among health and social scientists. However, it is unclear whether DOHaD‐based ideas are reaching the general public and/or influencing behaviour. This study thus investigated whether and under what circumstances pregnant people in Canada are familiar with DOHaD, and if DOHaD familiarity relates to eating behaviour. Survey responses from pregnant people from Hamilton, Canada, were used to assess respondents' knowledge of DOHaD (hereafter, DOHaDKNOWLEDGE ) compared with their knowledge of more general pregnancy health recommendations (Pregnancy GuidelineKNOWLEDGE ). The survey also characterized respondents' pregnancy diet quality and sociodemographic profiles. We fit two multiple, linear, mixed regression models to the data, one with DOHaDKNOWLEDGE score as the dependent variable and the other with diet quality score as the dependent. In both models, responses were clustered by respondents' neighbourhoods. Complete, internally consistent responses were available for 330 study‐eligible respondents. Relative to Pregnancy GuidelineKNOWLEDGE, respondents had lower, more variable DOHaDKNOWLEDGE scores. Additionally, higher DOHaDKNOWLEDGE was associated with higher socio‐economic position, older age, and lower parity, independent of Pregnancy GuidelineKNOWLEDGE . Diet quality during pregnancy was positively associated with DOHaDKNOWLEDGE, adjusting for sociodemographic factors. A subset of relatively high socio‐economic position respondents was familiar with DOHaD. Greater familiarity with DOHaD was associated with better pregnancy diet quality, hinting that translating DOHaD knowledge to pregnant people may motivate improved pregnancy nutrition and thus later‐life health for developing babies.